Automated Quantum Mechanical Predictions of Enantioselectivity in a Rhodium‐Catalyzed Asymmetric Hydrogenation. (28th June 2017) - Guan, Yanfei; Wheeler, Steven E.
Abstract: A computational toolkit (AARON: An automated reaction optimizer for new catalysts) is described that automates the density functional theory (DFT) based screening of chiral ligands for transition‐metal‐catalyzed reactions with well‐defined reaction mechanisms but multiple stereocontrolling transition states. This is demonstrated for the Rh‐catalyzed asymmetric hydrogenation of ( E )‐β‐aryl‐ N ‐acetyl enamides, for which a new C 2 ‐symmetric phosphorus ligand is designed.